1999
DOI: 10.1002/(sici)1521-3765(19990503)5:5<1570::aid-chem1570>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Theoretical Investigations of Electrophilic Bromination Reactions of Alkynes: The First Evidence for π Complexes as Reaction Intermediates

Abstract: A bromine ± alkyne p complex (l max 294 nm) of 1:1 stoichiometry has been observed for the first time in the course of the bromination of 1-phenylpropyne by means of a diode-array stopped-flow technique. ); this demonstrates that the complex is actually an essential intermediate on the reaction coordinate. The bromination of a series of nine alkynes has been studied. Bromination reactions with negative apparent activation parameters lead to mixtures of E and Z vinyl dibromides, whereas reactions with positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
1
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 35 publications
(56 reference statements)
9
53
1
6
Order By: Relevance
“…It seemed to be interesting for us to examine tetra-n-butylammonium tribromide (TBAT) as a brominating reagent. Literature data review reveals wide range of acetylenes being treated with this reagent give trans-1,2-dibromalkenes as the only products, result of the reaction being independent of its conditions and ratio of reagents [9].…”
Section: Bromination Of Element-substituted Phenylacetylenessupporting
confidence: 68%
See 1 more Smart Citation
“…It seemed to be interesting for us to examine tetra-n-butylammonium tribromide (TBAT) as a brominating reagent. Literature data review reveals wide range of acetylenes being treated with this reagent give trans-1,2-dibromalkenes as the only products, result of the reaction being independent of its conditions and ratio of reagents [9].…”
Section: Bromination Of Element-substituted Phenylacetylenessupporting
confidence: 68%
“…43 Earlier we reported that the treatment of N(CH 2 CH 2 O) 3 GeC CPh (1) with NBS/DMSO system affords N(CH 2 CH 2 O) 3 GeCBr 2 C(O)Ph and the reaction with bromine leads to the formation of cis-N(CH 2 CH 2 O) 3 GeC(Br) C(Br)Ph [7]. In contrast to this most of alkylatylacetylenes react with bromine in chloroalkanes under conditions of kinetic control to give a mixture of cis-and trans-dibromoalkenes, the latter considerably prevailing [8,9]. The addition of bromine to alkylphenylacetylenes containing strong electron-withdrawing para-substituents in the phenyl group is stereoselective and yields only the trans-dibromo adducts.…”
Section: Introductionmentioning
confidence: 89%
“…Although the stereochemical behaviour of the reactions of 1b and 1c was similar to that observed [21] in addition of Br 2 to the same alkynes in chlorinated solvents ( Table 2), that of 1a and 1d was significantly different. In particular, the reaction of 1a was characterised by a higher anti stereoselectivity.…”
Section: A Product Distributionssupporting
confidence: 62%
“…This species is known to add to alkenes [19] and alkynes [20] solvents by a mechanism that does not involve ionic intermediates and occurs through a product-and rate-determining attack by bromide on the olefinϪBr 2 π complex (Scheme 1). In contrast, the formation of both diastereoisomers in Br 2 addition to alkynes 1aϪd in [bmim][PF 6 ] indicated [5] that open vinyl cations (a) had been formed as intermediates, similarly to what has been observed [21] in 1,2-dichloroethane (DCE).…”
Section: A Product Distributionsmentioning
confidence: 99%
See 1 more Smart Citation